PENGUKURAN TINGKAT KEPUASAN PENGGUNA INTERNET NON-NASABAH TERHADAP WEBSITE BANK NEGARA INDONESIA (BNI) DENGAN WEBQUAL4.0 - Findi Ayu Sariasih; Yumi Novita Dewi (STIKOM CKI, 2018)
ABSTRACT This research is based on the extent to which the website of Bank Negara Indonesia (BNI) can be accepted by non-customer internet users, it is necessary to hold an assessment to measure available websites whether it is well received or not, so that the quality of websites based on user perceptions is important to know and make feedback on the provider. And can optimize the features and menus contained in it to be able to accommodate user needs related to the world of banking. The author uses the WebQual4.0 method, namely dimensions of usability (information usability), information quality (information quality), interaction quality (interaction quality), and overall impression (user satisfaction). As a result, 71.5% of user satisfaction is supported by these three factors and the hypothesis in this study is accepted as indicated by correlation techniques and multiple linear regression.